Ship Repair and Maintenance Management: Application of PERT Analysis on a Tanker Vessel - Turan, Eda; Asar, Ridvan (SOC NAVAL ARCHITECTS & MARINE ENGINEERS, 2020)
The costs in shipbuilding and ship repair and maintenance activities are massive and need several materials in the same production phase. Construction without planning is not rational, and any mistake in the planning phase will cause major loss of time, quality, and financial resources. Planning in ship repair and maintenance yards is more complicated than new building shipyards because the duration time is limited. In this study, 200-m-long tanker's repair and maintenance period has been planned by program evaluation and review technique analysis in light of the data acquired from X shipyard in Turkey to reflect critical activities that affect the total duration time.
Keywords: shipyard; repair; maintenance; planning; PERT; Engineering